A controlled trial of a nurse follow-up dietary intervention on maintaining a heart-healthy dietary pattern among patients after myocardial infarction - Mok, Vincent K F; Sit, Janet W H; Tsang, Alice S M; Chair, Sek Ying; Cheng, Tak Lai; Chiang, Chung-seung (The Journal of cardiovascular nursing, 2013)
Post-myocardial infarction (MI) survivors are at a higher risk of coronary events. Therapeutic lifestyle changes, including dietary modification, have been emphasized as the cornerstone of secondary prevention. This study aimed to examine the effectiveness of a nurse follow-up dietary intervention (NFDI) on post-MI patients' dietary behavioral change (primary outcome) and blood lipid levels (secondary outcome). A total of 82 post-MI subjects with borderline dyslipidemia were recruited and randomly allocated to a control group or an intervention group (IG) (n = 41/group). The control group received conventional care and attended a heart health dietary class. The IG received, in addition, a structured 8-week NFDI (including a face-to-face consultation session, a take-home self-management workbook, and fortnightly telephone follow-ups). Data were collected at 3 time points: baseline (T0), 1-week posttest (T1), 3-month posttest (T2). The effect of the intervention was assessed by a self-report questionnaire and blood tests. T test and time-by-group analysis of variance with repeated-measures analysis of variance were used. An intention-to-treat analysis was conducted. Significant positive dietary changes were found among participants of the IG in reduced intake of saturated fat (F = 22.48, P < .001) and salted/preserved food (F = 13.58, P < .001) and increased intake of heart-healthy food (vegetables, fruit, nuts, and whole grains) (F = 40.88, P < .001). Although the results of secondary outcomes, triglyceride, and total cholesterol were not statistically significant, the high-density lipoprotein trend was in the expected direction for the IG (F = 8.982, P = .001). This study found positive changes in dietary behavior and an increase in high-density lipoprotein level from participants who undertook the NFDI for self-management in dietary modification.